R-Spondin 2 Induces Odontogenic Differentiation of Dental Pulp Stem/Progenitor Cells via Regulation of Wnt/β-Catenin Signaling - Gong, Yuping; Yuan, Shuai; Sun, Jingjing; Wang, Ying; Liu, Sirui; Guo, Runying; Dong, Wenhang; Li, Rui (Frontiers in Physiology, 2020)
Odontoblast cells generated from human dental pulp stem/progenitor cells (hDPSCs) secrete reparative dentin in responds to an injury. Endogenous Wnt signaling is also activated during this process, and these Wnt-activated cells are responsible for the following repair response. R-spondin 2 (Rspo2) is a potent stem cell growth factor, which strongly potentiates Wnt/β-catenin signaling and plays a vital role in cell differentiation and regeneration. However, the role of Rspo2 during odontoblast differentiation in hDPSCs has not yet been completely understood. This study investigated the effects of Rspo2 on hDPSCs to provide therapeutic insight into dentin regeneration and reparative dentin formation. HDPSCs were extracted from human molars or premolars. Immunofluorescence staining and flow cytometric analysis were used to detect the mesenchymal stem cell markers in hDPSCs. EdU assay and Cell Counting Kit-8 (CCK-8) were performed to explore cell proliferation. The odontogenic differentiation levels were determined by measuring the mRNA and protein expression of DSPP, DMP-1, ALP, and BSP. Immunofluorescence staining was performed to detect the localization of β-catenin. The biological effects of Rspo2 on hDPSCs was investigated using the Lentivirus-based Rspo2 shRNA and recombined human Rspo2 (rhRspo2). Recombined human DKK-1 (rhDKK-1) and recombined human Wnt3a (rhWnt3a) were used for further investigation. The cells generated from human dental pulp expressed mesenchymal stem cell markers Vimentin, Stro-1, Nestin, C-kit, CD90, and CD73, while were negative for CD3, CD31, and CD34. The mRNA expression levels of the odontogenic-related genes DSPP, DMP-1, ALP, and BSP were upregulated in the rhRspo2 treated cells. Silencing Rspo2 suppressed the proliferation and differentiation of the hDPSCs. Blockade of Wnt signaling with DKK-1 inhibited Rspo2-induced activation of Wnt/β-catenin signaling and cell differentiation. The combined use of rhWnt3a and rhRspo2 created a synergistic effect to improve the activation of Wnt/β-catenin signaling. Rspo2 promoted the proliferation and odontogenic differentiation of hDPSCs by regulating the Wnt/β-catenin signaling pathway.